THE RUBAS FORTIFICATION OF THE MID-SIXTH CENTURY: STRUCTURAL FEATURES OF THE WESTERN FACADE OF WALL 2 - Gmyra, Ludmila Borisovna (History, Archeology and Ethnography of the Caucasus, 2022)
The Rubas fortification is a complex of stone military engineering structures, opened in 2014 in the lower reaches of the river. Rubas, 20 km SW from the city of Derbent. In terms of functional orientation, this archaeological object belongs to a series of monumental barrier structures erected in the Caspian Passage (Eastern Caucasus) by Sasanian Iran with the financial participation of Byzantium in the 5th–6th centuries, preventing raids of nomadic tribes into the countries of Transcaucasia and the Middle East. Typologically and chronologically (6th c.), the Rubas defensive complex is comparable to the stone fortifications of Derbent.Excavations (2014, 2016-2018, 2020) on the territory of the archaeological site revealed 6 separate military-technical structures. The connecting link in this complex is the main wall No. 2, oriented in the meridian direction (NW-SE), opened for 28 m. Three structures of the complex, oriented in the latitudinal direction (W-E), were connected to wall No. 2.Wall No. 2 is structurally distinguished by its monumentality. It was built using armored technique from massive, well-hewn stone blocks with internal backfilling from clastic material, including pebble stones and soil. The thickness of the wall is 3.2–3.5 m.A feature of the structure of wall No. 2 is that its facades (eastern and western) are combined. On the eastern facade, 5 building sections are visually distinguished, made using different technological methods. An analysis of engineering solutions during the construction of the eastern facade of wall No. 2 showed that they were due to certain functional tasks, both general defensive and specific, which ensured the strength of the building as a whole.
Keywords: Rubas fortification; East facade; main wall No. 2; structure of the western facade of wall No. 2; Sasanian Iran